Effect of annealing on the structural and optical properties of sputtered HfNx thin films. (1st January 2013) - Gueddaoui, H.; Schmerber, G.
HfNx films deposited by dc reactive magnetron sputtering at 150°C were annealed for 60 minutes at 400°C under a continuous 4.5 sccm argon gas flow. The X-ray diffraction (XRD) analysis of annealed films showed the existence of hexagonal (hcp-HfNx ) and rock-salt (fcc-HfNx ) phases in the chemical composition range 0.34 ≤ x ≤ 1.25. By using the Drude-Lorentz model, good agreement was found between experimental and calculated reflectance spectra in the energy range extending from 0.5 to 6.5 eV. The annealing treatment has two main effects: the first to increase the damping factor of the conduction of free carriers for x > 1.19 with a significant change in the plasma frequency, and the second to shift the screened plasma frequency towards lower energies.